(untitled) (INMR - Innovation & Management Review, 2023)
Purpose – Due to dramatic transformation of the auto industry, governments are implementing innovationpolicies to ensure the domain of sustainable technologies. According to the literature, developing countries thatdepend on multinational subsidiaries must invest in complementary innovation to be part of their research anddevelopment (R&D) headquarters’ long-term plans. This study analyses the Brazilian auto industry innovationpolicy (Rota 2030) to evaluate if it targets complementarity with the German’s one (NPE). It also compares theinstitutional arrangements of the former against the latter to check for governance gaps. Design/methodology/approach – It applies a case-oriented comparative method (Ragin, 2014) for theanalysis of qualitative evidence on secondary data. It investigates evidence of complementarity between Rota2030 and national platform for electric mobility (NPE) objectives and checks for governance gaps in Rota 2030using NPE as a reference. Findings – The results confirmed a loose fitting between the innovation policies mainly for a lack ofdeterminism of Rota 2030 objectives. Governance gaps were also found on Rota 2030 policy formulation andoperationalization. Practical implications – It contributes for the improvement of Rota 2030, and its analytical frame may beused for the formulation or adjustment of other developing countries’ innovation policies. Originality/value – It contributes with innovation system and policy field development with a theoreticalextension coming from the New Institutional Economics (NIE) (Menard, 2018). By examining the performanceof“institutional arrangements” during the process of formulation and operationalization of innovation policies,it shows the importance of coordination for their effectiveness